Tughral Yamin, The Evolution of Nuclear Deterrence in South Asia - Ms. Kulsoom Belal (CISS Insight Journal, 2014)
Dr. Tughral Yamin’s The Evolution of Nuclear Deterrence in South Asia is his first book. The book is based on the work done by him for his doctoral dissertation but has been updated to address the current developments and issues. His recently published second book is Cyberspace CBMs between Pakistan and India. Yamin specializes on the issues of strategic stability and regional peace, confidence building measures and conflict resolution. The author has served in the Pakistan Army and retired as a brigadier. Currently he holds the position of Associate Dean at Center for International Peace and Stability (CIPS), National University of Sciences and Technology (NUST). In The Evolution of Nuclear Deterrence in South Asia, the author argues that the dynamics of strategic stability inherent in the possession of nuclear weapons is as much applicable in the South Asian environment as it was during the Cold War period. Although the Cold War has become an over-analyzed subject the writer uses this as a context to discuss the significance of nuclear weapons in bringing stability between India and Pakistan.